2017
DOI: 10.1371/journal.pone.0173088
|View full text |Cite
|
Sign up to set email alerts
|

Differential depletion of total T cells and regulatory T cells and prolonged allotransplant survival in CD3Ɛ humanized mice treated with polyclonal anti human thymocyte globulin

Abstract: Thymoglobulin (ATG) is a polyclonal rabbit antibody against human thymocytes used as a T cell-depleting agent to prevent or treat allotransplant rejection. The aim of the present study was to investigate the effect of low dose ATG treatment exclusively on T cells using a humanized BALB/c human CD3Ɛ transgenic mouse model expressing both human and murine T cell receptors (TCR). Mice received a single intravenous (i.v.) injection of ATG. Blood and peripheral lymphoid organs were obtained after different time poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…ATG is a lymphocyte-depleting polyclonal antibody that targets multiple immunological epitopes. There are several ATG preparations, which differ from regard to the source of human T cells and the inoculated animals [3,4]. Basiliximab is a monoclonal antibody that targets the interleukin-2 receptor [14].…”
Section: Introductionmentioning
confidence: 99%
“…ATG is a lymphocyte-depleting polyclonal antibody that targets multiple immunological epitopes. There are several ATG preparations, which differ from regard to the source of human T cells and the inoculated animals [3,4]. Basiliximab is a monoclonal antibody that targets the interleukin-2 receptor [14].…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigations demonstrated that the same monoclonal Abs that efficiently eliminate or inhibit effector T cells actually spare Foxp3 + Tregs, in contrast [13][14][15][16][17][18]. Similar observations were reported after treatment with anti-lymphocyte serum or anti-thymocyte globulin [28][29][30][31][32]. Consequently, Treg frequency (but not necessarily absolute numbers) increases in lymphoid organs and in the grafts, thus creating a local Treg-enriched microenvironment amenable to the induction of immune tolerance, and referring to an "immune privileged site" [33].…”
Section: Relative Role Of Foxp3 + Tregs For the Acquisition And The Mmentioning
confidence: 59%
“…Kinetics of PBLS after LTx distinguished 2 consecutive phases in relationship with the immunosuppressive therapy. In the very early postoperative phase, there was not only a strong T cell depletion, as expected with the induction therapy with ATG [ 22 , 23 ], but also a decrease in NK cell counts. The impact of ATG on NK cells has already been reported in kidney transplantation [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 86%